Tuning Ion/Electron Conducting Properties at Electrified Interfaces for Practical All‐Solid‐State Li–Metal Batteries. (22nd June 2022) - Guo, Junze; Zhang, Weidong; Shen, Zeyu; Mao, Shulan; Wang, Xinyang; Zhang, Shichao; Zhang, Jiahui; Lu, Yingying
Abstract: Poly(ethylene oxide) (PEO) based solid‐state electrolytes with good chemical stability against Li–metal, provide a promising solution for practical all solid‐state Li–metal batteries (ASSLMBs). However, the risk of short circuit using thin PEO under semi‐molten state and the oxidative decomposition of PEO by cathodes under high voltage hinder the practical application of PEO‐based ASSLMBs. Here, it is found that by readjusting the Li + and e – conductivity at anode/cathode interface by introducing Nanodiamonds (NDs) into PEO electrolytes can greatly improve the electrochemical performance of PEO‐based batteries. Under the mediation of high modulus and insulative NDs, the lifespan of Li symmetric cells can increase by 30 times at 0.8 mA cm –2, and high‐voltage Li/LiCoO2 cells show excellent capacity retention under practical testing conditions (50 µm Li and 30 µm PEO electrolyte). Abstract : With the introduction of Nanodiamonds, Li + and e − conductivity at anode/cathode interface can be readjusted in poly(ethylene oxide) (PEO) based all solid‐state Li–metal batteries, which can dramatically improve the capacity retention of high‐voltage Li/LiCoO2 under practical testing conditions (50 µm Li and 30 µm PEO electrolyte).